2012
DOI: 10.1007/s10035-012-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of inter-particle friction and the intermediate stress ratio on soil response under generalised stress conditions

Abstract: Previous research studies have used either physical experiments or discrete element method (DEM) simulations to explore, independently, the influence of the coefficient of inter-particle friction () and the intermediate stress ratio (b) on the behaviour of granular materials. DEM simulations and experiments using photoelasticity have shown that when an anisotropic stress condition is applied to a granular material, strong force chains or columns of contacting particles transmitting relatively large forces, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(62 citation statements)
references
References 22 publications
8
53
1
Order By: Relevance
“…The asymptote is referred to as the deviatoric steady state or the macroscopic friction, where represents the mobilized friction at each step along the loading path. For lower volume fractions, higher maximum are reached and the deviatoric stress ratio increases faster, meaning a higher ratio, where is the octahedral shear modulus as defined by Barreto and O Sullivan, 2012. This is opposite to what is expected for the shear modulus itself, being proportional to the volume fraction.…”
Section: Deviatoric Stresscontrasting
confidence: 48%
“…The asymptote is referred to as the deviatoric steady state or the macroscopic friction, where represents the mobilized friction at each step along the loading path. For lower volume fractions, higher maximum are reached and the deviatoric stress ratio increases faster, meaning a higher ratio, where is the octahedral shear modulus as defined by Barreto and O Sullivan, 2012. This is opposite to what is expected for the shear modulus itself, being proportional to the volume fraction.…”
Section: Deviatoric Stresscontrasting
confidence: 48%
“…To date, considerable studies using DEM have been conducted to investigate the shear behavior of granular materials under a complex stress path [10][11][12][13]. In these studies, DEM simulations of polydisperse spherical particle systems were performed under constant mean stress (or constant minor principal stress) with varying b values.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a scarcity of large-strain laboratory test data for 3D general loading conditions; this limits the ability to develop and to apply these models to field applications where the stress state is not axisymmetric. Prior studies simulating true-triaxial element tests (Thornton 2000;Ng 2004;Barreto & O'Sullivan 2012; have shown that DEM can replicate the failure envelopes proposed for real sands. Thus, if a DEM model can be shown to capture the sensitivity of the material response to ψ that one would expect for a real sand, there is then potential to use DEM to advance critical state-based constitutive models for sand.…”
Section: Introductionmentioning
confidence: 99%